INSEKTA NOKTURNAL YANG DITEMUKAN DI PERKEBUNAN TEBU RAKYAT NAGARI LAWANG KECAMATAN MATUR KABUPATEN AGAM SEBAGAI SUMBANGSIH PADA MATERI KEANEKARAGAMAN HAYATI UNTUK TINGKAT SMA/MA - Syafnita, Bunga Ayu; Abizar, Abizar; Zikra, Zikra; Syafitri, Elza (FKIP Universitas Tanjungpura, 2026)
Nagari Lawang, Matur District, Agam Regency, West Sumatra, is an agricultural area dominated by sugarcane (Saccharum officinarum) plantations, characterized by hilly topography at an altitude of 900–1,200 m above sea level, a cool climate, and high humidity that support nocturnal insect diversity. This study aimed to identify nocturnal insect species in community sugarcane plantations and to develop an educational blog as learning media for Animalia topics. The research employed a descriptive survey method with direct field sampling using a light trap (light trap) and random sampling technique. A total of 23 nocturnal insect species belonging to 6 orders and 21 families were recorded. Species identification was conducted based on standard taxonomic references, including Borror and White (1970), Achterberg van K. (1991) Volumes I and II, and identification keys from the Indonesian Journal of Entomology.